(3QSGdI aj GdCcSjQs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb ef YGde GdaSGO HTQkG hYXeI hHYO adeG bOQ Gddg HZQHJi hLhdGfi ai CjGe SjGMJi Ke SGbJfi GdeTjFI Edi Cf ONdJ HRfWjI s
(3BNQgG (B:s
(3Ke JJQcg Edi Cf jMeO agh GcSjQ JGe HYO ZSjd HNGQg hgh RGFO Ydi PgH GdYGeI HYTQI bQGQjW s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3gPg GdQSGdI HGSe GdSdWGf SdjeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs